Análise dos gases da exaustão em um motor diesel com injeção Common Rail alimentado com diesel, biodiesel e suas misturas - Costa, Joel de Oliveira (2017)
The presente work aims to evaluate exhaust gas emissions and particulate matters in a diesel cycle engine. A Cummins ISB Maxi Power (EURO III) Ford F250 pickup truck with electronic commom rail fuel injection system was used to identify which blend achieves the best environmental performance without compromising power and torque. The exhaust gases (CO, NOx, SO2) and particulate matters in different engine operating regimes were analyzed using commercial diesel oil B7 (diesel oil with 7% biodiesel volume) and additions of biodiesel up to B100. The procedures used in the tests were based on the ESC (European Stationary Cycle) test of engines in chassis dynamometer. The dynamometer used was the BOSCH model FLA 203, in conjunction with a TESTO model 350 gas analyzer, a NAPRO model NA 9000 opacimeter, and a 24-channel Pro Model FUEL TECH Datalogger. The results showed that the carbon monoxide (CO) had a significant reduction of 57.22% with the engine running with B100 at 750 rpm and 84.39% at 2600 rpm in a regime of 75% of the maximum power compared to B7. Nitrogen oxide (NOx) had an increase of 145.43% with B100 at 2600 rpm. Sulfur dioxide (SO2) produced by the combustion of diesel S10, represents low values, reaching 0 ppm in any of the engine operating regimes operating with the blends. The power and torque of the engine had an increase of 2.85% and 2.81% with the B15 mixture compared to the B7 fuel, even with the B15 we can verify that the carbon monoxide (CO) had a reduction of 35.78%, nitrogen oxides (NOx) had an increase of 40.71% and opacity a reduction of 1.9%.